Topology Design and Kinematics for a Novel Semi-symmetric 2T1R Parallel Mechanism with Low Coupling Degree - Hao Ji; Huiping Shen; Tingli Yang (Jixie chuandong)
According to the topology design theory and method of parallel mechanism(PM) based on position and orientation characteristic(POC) equations， a novel semi-symmetrical PM with two translation and one rotation (2T1R) output motion is designed. And the three main topological characteristics of the PM， such as the POC， degrees-of-freedom (DOF) and coupling degree are calculated and analyzed， and the coupling degree of the mechanism is 1.Then， based on the kinematics modeling principle of the ordered single open chain (SOC) units， the positive kinematics solution and inverse kinematics solution formula are achieved. According to formula， the workspace and rotational ability of PM are got and analyzed. The singularity condition of mechanism is studied. The velocity and acceleration of the mechanism are simulated and analyzed. Finally， the principle of the mechanism applied to ankle massage is analyzed.